Engaging the world : the use of empirical research in bioethics and the regulation of biotechnology - Holm, Søren, 1963-; Jonas, Monique F. (Biomedical and health research ;, 2004)
Holm (Institute of Medicine, Law, and Bioethics, University of Manchester, UK) and Jonas (Center for Social Ethics and Policy, University of Manchester) gather papers representing the work performed as part of the Empirical Methods in Bioethics project sponsored by the European Commission, DG-Research. The papers are mainly concerned with investiga.